On some topological properties of generalized difference sequence spaces defined - Turan, G.A. (Academic Publications Ltd., 2017)
In this paper, we define new generalized difference sequence spaces ?? M (? v m, u) and ? N ? (? v m, u) where M =(Mk) and N= (Nk) are sequences of Orlicz functions such that Mk and Nk are mutually complementary for each k. We also examine some topological properties and establish some inclusion relations between these spaces. © 2017 Academic Publications.
Keywords: Difference sequence spaces; Orlicz function